Lived experiences of people with chronic kidney disease on maintenance dialysis: a systematic review and thematic synthesis of qualitative studies - Maya Annie Elias; Wim Van Damme; Grace Marie V Ku; Mahesh Kadammanavar; Edwin Wouters (BMC Nephrology)
Abstract Aim Chronic Kidney Disease (CKD) has emerged as a global public health concern. People with the most advanced stage of CKD require renal replacement therapies, either dialysis (the focus of this study) or a kidney transplant. Research on CKD has primarily focused on its clinical, epidemiological, and public health aspects. However, studies exploring the lived experiences of individuals on dialysis and the key factors influencing these experiences are limited, particularly in low- and middle-income settings. Therefore, this study aims to synthesize the existing literature on the illness experience of people living with CKD who are on maintenance dialysis across different country contexts. Methods Adhering to PRISMA and PiCO guidelines for systematic review, we identified original studies published between 2000 and 2024, focusing on the lived experience of patients with CKD on dialysis, across PubMed, Web of Science, and Scopus databases. A thematic analysis was conducted based on two frameworks: Michael Bury’s biographical disruption model of chronic illness, and the framework on internal and external factors affecting self-care. Results A total of 59 studies were included, and the following key themes were identified: 1) disrupted biographies among people on dialysis, which included: (a) diagnosis and initiation of dialysis, (b) disabling physical symptoms and functional limitations, (c) impaired socio-occupational functioning, (d) uncertainty and psychological distress, and (e) changes in self-image and identity; and 2) biographical repair, which included: (a) coping with CKD and dialysis, (b) coping styles, and (c) coping strategies. The key internal factors influencing the lived experiences were personal beliefs and misconceptions about CKD, feelings of shame and guilt, financial constraints, and spirituality. The external factors included family and social support, information and treatment received from the clinical team, social stigma, availability and quality of dialysis services, and access to health insurance. Conclusions This review deepens our understanding of the lived experiences of individuals undergoing maintenance dialysis across diverse settings and illuminates the internal and external factors that shape these experiences. Our findings emphasize the necessity of a holistic and person-centred approach to dialysis care and highlight the need to make dialysis services more accessible and affordable in low- and lower-middle-income countries.